Marketing dictatorship : propaganda and thought work in contemporary China - Brady, Anne-Marie, 1966- (Asia/Pacific/perspectives., 2008)
"In this important book, noted China scholar Anne-Marie Brady answers some intriguing questions about China's contemporary propaganda system. Why have propaganda and thought work strengthened their hold in China in recent years? How has the CCP government strengthened its power since 1989 when so many analysis predicted otherwise? How does the CCP maintain its monopoly on political power while dismantling the socialist system? How can the government maintain popular support in China when the uniting force of Marxist-Leninist-Maoist ideology is spent and discredited? What has taken the place of communist ideology? Examining propaganda and thought work in the current period offers readers a unique understanding of how the CCP will address real and perceived threats to stability and its continued hold on power. This innovative book is a must-read for everyone interested in China's growing role in the world community."--Jacket